OC-078 Combined histo-cytological analysis of eus-fna samples from solid lesions using standard fna needles gives better diagnostic yield and accuracy. (17th June 2017) - Banerjee, AK; Cairns, A; Sanni, L; Paranandi, B; Huggett, M
Abstract : Introduction: Diagnostic yield from EUS-FNAC (fine needle aspiration cytology) has improved in the past few years with better tissue acquisition techniques. Core biopsy needles are now available but are more expensive than FNAC needles. We assessed the diagnostic yield and accuracy of FNAC samples processed for both cytology and histology. Method: EUS-FNA samples of solid lesions (from September 2014 to September 2016) were included in a prospective audit of practice. Between September 2014 and January 2016 the standard practice was to send FNAC samples for cytology only. After this date, FNAC samples were filtered through a cassette. The solid material was sent in formalin to histology and the effluent to cytology for cytospin and cell block as previously. Cellularity was graded as adequate or inadequate. Final diagnosis was obtained from MDT outcomes. Results: A total of 211 patients (118 male) were included. Samples were sent to cytology (n=135; 107 pancreas, 10 biliary, 7 lymph nodes, 11 other), or cytology and histology (n=76; 56 pancreas, 12 biliary, 5 lymph nodes, 3 other). Sample adequacy was 80.7% and 98.7% (p=0.0004). Diagnostic yield (64.4%, 94.7%) and accuracy (81.3%, 96.1%) was significantly better in the combined (histology and cytology) group (p<0.0001, p=0.003). Within the combined group, diagnostic yield and accuracy improved by 20.5% (p=0.007) and 26% (p=0.0002) respectively when the sample was processed for both cytology and histology. Conclusion: Our study confirms significant improvement in diagnostic yield and accuracy when samples were sent for both cytology and histology using standard FNAC needles. Disclosure of Interest: None Declared